Beyond knowledge acquisition: factors influencing family planning utilization among women in conservative communities in Rural Burundi - Sonia Hakizimana; Emmanuel Nene Odjidja (BMC, 2021)
Plain Language Summary In the Burundian context, community members agree that large family sizes are difficult to maintain, yet use of family planning remains consistently low. This study explored the factors behind this low utilisation of family planning in two health districts located in the South of Burundi. The findings suggest that fear of side effects is the main reason for family planning non-utilization or discontinuation. The culture and religious beliefs in Rural Burundi also espouse large family sizes and among men, this is conceived as a sign of wealth, power, and respect. Lack of spousal communication and unequal gender relations in household also impedes women from contributing decisions on family planning. The onus on making decisions on contraceptive use lies on men, whom usually, have limited understanding of family planning methods. In improving coverage of family planning in these communities, capacity of the health system to provide quality, timely and people-driven family planning services should be strengthened. At the community level, the use of community health workers to deliver family planning services to the doorstep of community members could significantly increase uptake. Finally, men and religious leaders' involvement in promoting family planning use can contribute to reducing the impact of cultural and religious barriers to uptake.